The fourth book of Ezra in Russian social and religious thought of the 16th – 18th centuries - Igor Bessonov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2025)
The subject of this article is the use of the Fourth Book of Ezra in Russian social and religious thought of the 16th-18th centuries. This work was translated into Church Slavonic from Latin at the end of the 15th century and until the mid-18th century it was part of the main text of the Old Testament. At the beginning of the 16th century, the Fourth Book of Ezra was used as a source of cosmographic information (letter from Fyodor Karpov to Maxim the Greek). At the same time, the attention of readers began to be attracted by the image of a three-headed eagle (4 Ezra 11), which evoked associations with a two-headed eagle, which, starting in 1497, was the emblem of the Moscow state. In the 17th century, this image became central in the perception of the Fourth Book of Ezra by Russian readers. Thus, the Old Believers saw in the image of an eagle a prophecy about a king (or several kings), whom they identified with the Antichrist. Yuri Krizhanich, who criticized the concept of the Third Rome, on the contrary, denied the connection between the eagle from the Fourth Book of Ezra and the Russian state. In the 18th century, the Fourth Book of Ezra gradually ceased to be used by supporters of the official Church and continued to be actively read and commented on only among the Old Believers.